Exploring therapeutic process through music therapy : the experience of an adult "Third Culture Kid" - Lin, Oushu (2020)
In the background of globalization, Third Cultural Kids (TCKs) benefit for multilingual, open-minded and as so-called a global citizen. Meanwhile, they are potentially facing various challenges in mental health areas, such as feeling rootlessness, facing disenfranchised grief and difficulties in developing positive relationships. This thesis presented a unique case study of how music therapy approaches, and interventions encounter the needs of the client who has grown up as a TCK. Exploring the therapeutic process, the writer will look closely to how does the client, an Adult TCK, recreate her moments of vulnerability in music therapy sessions and how does the music therapist react to “at the moment” needs and potentially promote long term psychological well-being. However, to outline the complex story of this individual client is not aiming for providing a solution to TCKs’ related problem, but rather to raise the understanding and insightfulness toward the phenomenon occurred in the therapeutic process. The author herself has been working closely with TCKs in multiple international schools, and she has also experienced acculturation while spending adulthood aboard. She somehow paralleled her experiences while observing the sessions and qualitative data in this case study. Being empathetic with the client’s TCK experiences has brought her up to study how music therapy process related to underlying TCKs’ psychological profile and to achieve the potential therapeutic needs.